Effect of Work Competency and Work Environment on Work Motivation and Organizational Commitment of Employees University of Jabal Ghafur Sigli - Fakhrurrazi, Fakhrurrazi; Boihaki, Boihaki (Budapest International Research and Critics University, 2022)
This research was conducted with the aim of testingthe influence of competence and work environment on work motivation, and organizational commitment of employees of the University of Jabal Ghafur Sigli. This research was conducted at the University of Jabal Ghafur Sigli Pidie District, The object of this research is all employees Jabal Ghafur University. The sample in this study was 161 respondents.The data used in this study is primary data sourced from 161 respondents. The data analysis method used was Structural Equation Modeling (SEM) with AMOS 22. The results showed that the variables of work competence and work environment had a positive effect on work motivation. The results of the mediation variable test show that work motivation partially mediates the relationship between work competence and organizational commitment.Work motivation fully mediates the relationship between the environment and organizational commitmentJabal Ghafur Sigli University employee.